The Relationship Between Family Support and Adolescent Visits to the Adolescent Integrated Health Post (Posyandu) in The Working Area ff The Sei Rahayu Community Health Center - Siti Yuniawati; Anik Sri Purwanti (Garuda Pelamonia Jurnal Keperawatan, 2026)
Background: Adolescence is a critical period of growth and development that requires optimal health services, including participation in the Adolescent Integrated Health Post (Posyandu Remaja). Family support plays an important role in encouraging adolescents to utilize health services. However, adolescent visits to Posyandu Remaja in the working area of the Sei Rahayu Community Health Center are still relatively low, indicating the need to examine factors influencing attendance, particularly family support. Objective: This study aimed to analyze the relationship between family support and adolescent visits to the Adolescent Integrated Health Post (Posyandu Remaja) in the working area of the Sei Rahayu Community Health Center. Methods: This study employed a quantitative analytical design with a cross-sectional approach. The sample consisted of 30 adolescents selected using a total sampling technique. Data were collected using structured questionnaires to assess family support and adolescent visit behavior. Data analysis was performed using the Wilcoxon test. Results: The results of the Wilcoxon test showed a significant relationship between family support and adolescent visits to Posyandu Remaja, with a p-value of 0.000 (p < 0.05). Adolescents who received good family support were more likely to attend Posyandu Remaja regularly compared to those with low family support. Conclusion: There is a significant relationship between family support and adolescent visits to the Adolescent Integrated Health Post (Posyandu Remaja) in the working area of the Sei Rahayu Community Health Center. Strengthening family involvement is essential to increase adolescent participation in Posyandu Remaja activities.